2019
DOI: 10.3747/co.26.4593
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Human T Cell Lymphotropic Virus 1 Infection in Canada

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Staphylococcus aureus, Mycobacterium leprae, Chlamydophila pneumoniae , and dermatophytes are among some of the infectious agents implicated as triggers/promoters of CTCL. Moreover, certain viruses investigated for their role in triggering CTCL include Human T-cell leukemia/lymphotropic virus type 1 (HTLV-1) , which was consistently associated with Adult T-Cell Lymphoma (39), but not MF/SS (4046). Further, HTLV-2 (41, 47), HIV (36, 48, 49), Epstein-Barr virus (5061), Cytomegalovirus (62, 63), Human Herpesvirus (HHV)-6, HHV-7 (57, 6466), HHV-8 (67) and even Polyomaviruses including Merkel cell polyomavirus (MCV) (6870) were also proposed to play an important role in disease pathogenesis.…”
Section: Environmental and External Risk Factors Of Ctclmentioning
confidence: 99%
“…Staphylococcus aureus, Mycobacterium leprae, Chlamydophila pneumoniae , and dermatophytes are among some of the infectious agents implicated as triggers/promoters of CTCL. Moreover, certain viruses investigated for their role in triggering CTCL include Human T-cell leukemia/lymphotropic virus type 1 (HTLV-1) , which was consistently associated with Adult T-Cell Lymphoma (39), but not MF/SS (4046). Further, HTLV-2 (41, 47), HIV (36, 48, 49), Epstein-Barr virus (5061), Cytomegalovirus (62, 63), Human Herpesvirus (HHV)-6, HHV-7 (57, 6466), HHV-8 (67) and even Polyomaviruses including Merkel cell polyomavirus (MCV) (6870) were also proposed to play an important role in disease pathogenesis.…”
Section: Environmental and External Risk Factors Of Ctclmentioning
confidence: 99%
“…In addition, in accordance with the institutional policy, this study received an exemption from McGill University research ethics board review. This work was performed in a manner similar to that previously reported . Incidence data for MM and PCL were obtained from the Canadian Cancer Registry (CCR) for cases occurring in provinces outside Quebec and from le Registre Québécois du Cancer (LRQC) for cases in Quebec, whereas all mortality data were obtained from the Canadian Vital Statistics (CVS) database.…”
Section: Methodsmentioning
confidence: 99%
“…Accepted risk factors for MM include a positive family history, an advanced age, black race, and male sex, with an elevated risk also being demonstrated for activities leading to obesity or a poor diet and a lower socioeconomic status . Studies assessing environmental and occupational exposures worldwide have consistently shown an elevated risk of MM in farmers and in individuals exposed to pesticides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Demographic and geographic data were obtained from the Canadian Cancer Registry (CCR), Le Registre Québécois du Cancer (LRQC), and the Canadian Vital Statistics (CVS) databases, as described previously. 13,14,[16][17][18][19][20][21][22][23][24][25][26] The CCR is a national database of cancer patients from 12 Canadian provinces and territories (excluding Quebec) who were diagnosed with primary tumors between 1992 and 2014. The LRQC database was used to obtain corresponding data for patients residing in Quebec.…”
Section: Methodsmentioning
confidence: 99%